Secondary Pyroelectric Effect and Figure of Merit of Ferroelectric 0–3 Composites - Ando, Daisuke; Eichhorn, Franziska; Fey, Tobias; Kakimoto, Ken ichi (Advanced Engineering Materials, 2019)
By mixing lead-free piezoelectric Li0.06(Na0.50K0.50)0.94NbO3 (LNKN) ceramic particles and polysiloxane, the authors synthesize a novel pyroelectric element that exhibits an enhanced secondary pyroelectric effect. The composite with an LNKN filler ratio of 30 vol% exhibits a homogeneous microstructure and a strong contact between the LNKN filler and the polysiloxane matrix. Thus, the secondary pyroelectric effect originating from such an interaction accounts for approximately half of the total pyroelectric coefficient (i.e 29 μC/m2K) and enhanced the figure of merit of the composite (1.1 μC/m2K).
CRIS-Team Scopus Importer:2019-06-18
Keywords: composite; lead-free piezoelectric material; pyroelectric; secondary pyroelectric effect; thermal expansion